The Sociology of Development and Underdevelopment: Are There Lessons for Economics? - W. Ruttan, Vernon (The International Journal of Sociology of Agriculture and Food, 2021)
Economists have seldom drawn knowledge from sociology in their analysis of the development process. In this paper I attempt to evaluate the contributions of sociologists who have worked within the traditions of modernization theory and of dependency and world systems theory in terms of their potential contributions to research by development economists. I conclude that metatheory in sociology has little to offer economists at this stage and that I should extend my review to cover a number of "middle range" theories that are more directly related to applied research by development economists.?ResumenLa Sociología del Desarrollo y del Subdesarrollo: ¿Tiene Lecciones para los Economistas??Los economistas rara vez toman en cuenta a la sociología en sus análisis del proceso del desarrollo. En este articulo intento evaluar las contribuciones de los sociólogos que han trabajado dentro la tradición de la teoría de la modernización y de la dependencia, asi como, de la teoría del sistema mundial, en términos de sus potenciales contribuciones para los economistas que investigan el desarrollo. Concluyo que la metateoría sociológica tiene poco que ofrecer a los economistas en éste nivel, por lo que extendí mi revisión para cubrir un número de teorías de "alcance medio" que están más directamente vinculadas con la investigación aplicada por economistas del desarrollo.